Disasters : natural and man-made catastrophes through the centuries - Guiberson, Brenda Z. (New York : Square Fish, 2010)
In these riveting chapters about well-known disasters, such as the Great Chicago Fire, the sinking of the Titanic, and Hurricane Katrina, Brenda Guiberson explores the cause and effect as well as the local and global reverberations. Highlighted with photographs and drawings, each compelling account tells the story of destruction and the power of mankind to persevere in the face of adversity.
Keywords: Disasters; Natural disasters; Juvenile; Juvenile literature